Pemanfaatan Media Online Quizizz dalam Optimalisasi Pelaksanaan Kegiatan Belajar Mengajar (Studi Kasus SMA Negeri 5 Balikpapan) - Kinanthi Nur Afifah Anastasya Rusmawan; Maharani Ikaningtyas (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Current technological developments are closely related to the millennial generation learning system and from elementary schools to tertiary institutions. This phenomenon is closely related to the use of learning software based on information and communication technology. Technology development with the Quizizz application is the right choice because Quizizz makes learning fun, challenging and interactive and adds to the knowledge, education and creativity of participating educators. A paradigm shift where learning develops with the application of technology that continues to grow rapidly, so it is not outdated and boring. This learning requires active learning, interactive communication and participation between students and teachers. Learning activities must also be created to achieve learning objectives.